2022
DOI: 10.3390/biology11121811
|View full text |Cite
|
Sign up to set email alerts
|

Consequential Impact of Particulate Matter Linked Inter-Fibrillar Mitochondrial Dysfunction in Rat Myocardium Subjected to Ischemia Reperfusion Injury

Abstract: A previous study has reported that exposure to PM2.5 from diesel exhaust (diesel particulate matter (DPM)) for 21 days can deteriorate the cardiac recovery from myocardial ischemia reperfusion injury (IR), where the latter is facilitated by the efficiency of mitochondrial subpopulations. Many investigators have demonstrated that IR impact on cardiac mitochondrial subpopulations is distinct. In the present study, we decipher the role of PM2.5 on IR associated mitochondrial dysfunction at the subpopulation level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Throughout the entire experiment, hemodynamic parameters were continuously monitored using AD instruments’ Lab chart software (LAB CHART PRO) from Australia. At the end of the experiment, the hearts were collected and preserved for subsequent analysis [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the entire experiment, hemodynamic parameters were continuously monitored using AD instruments’ Lab chart software (LAB CHART PRO) from Australia. At the end of the experiment, the hearts were collected and preserved for subsequent analysis [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the interaction between PM 2.5 exposure and myocardial ischemia-reperfusion (IR) injury, a condition characterized by the temporary interruption and subsequent restoration of blood flow to the heart, presents an additional challenge [ 15 , 16 ]. IR injury is a significant contributor to myocardial damage, and understanding its pathophysiology is crucial to improving clinical outcomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since small particles of ≤10 µm are found in the air, it is believed that the only organ that can be damaged is the lung and therefore could only induce respiratory diseases. However, epidemiological studies have reported a relationship between PM 2.5 and the cardiovascular system resulting in hypertension, atherosclerosis, myocardial infarction, heart attacks, and alterations in heart rate ( Barr et al, 2012 ; Jacobs et al, 2012 ; Madrigano et al, 2013 ; Sivakumar et al, 2022 ; Mordukhovich et al, 2015 ; Kirrane et al, 2019 ; Hayes et al, 2020 ). Also, several studies reported the presence of electrocardiogram alterations such as ST-segment changes and T-wave amplitude alterations ( Chuang et al, 2008 ; Gardner et al, 2014 ).…”
Section: Pm Accumulation In Human Tissuesmentioning
confidence: 99%